A kingdom of blood and betrayal - Renee, Holly (A Kingdom of Stars and Shadows, 2025)
"A fate bound to two princes-one born of blood, the other of power. When the dark prince offers me a bargain that will save his people and my life, the cruelly intoxicating fae gives me no choice. Our union is his revenge, and I am his sacrifice. His lies are unforgivable. His wicked touch bathes me in sin. He is my mate, and he is tortured by a curse to protect his people from his own family-from my allies. I can now see him for exactly who he is. So why can't I get his alluring touch out of my head? I am the key to saving his kingdom, but he alone has the power to ruin me"--